Isolation and partial chemical characterization of macrophage-derived neutrophil chemotactic factor - M. Dias-Baruffi; M. C. Roque-Barreira; F. Q. Cunha; S. H. Ferreira (Mediators of Inflammation)
Macrophages stimulated with lipopolysaccharide (LPS) release a factor (MNCF; macrophage-derived neutrophil chemotactic factor) which induces neutrophil migration in vivo and in vitro. The in vivo chemotactic activity of crude MNCF is not affected by pretreating the animals with dexamethasone, an uncommon characteristic which discriminates MNCF from known chemotactic cytokines. We purified MNCF by affinity chromatography of the supernatant from LPS-stimulated macrophages on immobilized D-galactose, followed by gel filtration of the sugar-binding material on Superdex 75. The activity was eluted in the volume corresponding to a MW of 54 kDa. SDS–PAGE of this preparation revealed a single band, also corresponding to a 54 kDa protein. MNCF is an acidic protein (pI < 4) as shown by chromatofocussing. Like the crude MNCF, the homogeneous protein induced neutrophil migration in vitro as well as in vivo. This was not modified by dexamethasone pretreatment.